Bitcoin Economy: Cryptocurrency Ecosystem Analysis and Long-Term Projections - Robert Cooper (International Journal of Science and Society, 2022)
Bitcoin is an innovative digital currency that came out in 2009 and prepared the scene afterwards for numberless cryptocurrencies to circulate in the market. Bitcoin had become an asset used by more individual thanks to its market capitalization, increasing number and volume of transactions day by day and more stabilized market price in this period. Technically, Bitcoin uses an infrastructure called block-chain that includes all transaction logs and let the user to confirm the validity of these transactions. In financial terms, Bitcoin is an asset that has regular fiat money functions such as being a medium of exchange, measure of value, standard of deferred payment and store of value in some way. At the same time, Bitcoin constitutes a new economy consisting mining firms in the process of minting new currencies, e-wallet applications that keeps the currency securely in individual and institutional accounts, financial services that focus on technical infrastructure and/or provide technical analysis service on market value, exchange markets that serves as a market that ensures the exchange transactions and trades, payment processors that allow usage of the currency as medium of payment in purchase and sale processes and lastly firms that operates at least two of these sub-sectors or more. This new economy brought along new opportunities and has been attracted the venture capital to itself. This study aims to acquaint about Bitcoin and the related new economy formed by sub-sectors. This study therewithal intends to develop a perspective about the future of this new economy and might serve as a premise study for forthcoming researches.